Legitimacy, distantiation and the ecology of knowledge production in the Norwegian asylum procedure - Rosset, Damian (My University, 2018)
The strict separation between the production of country of origin information (COI) and the assessment of asylum applications is a fundamental norm in the professional practice of COI producers. By looking at the Norwegian COI unit, this article examines the way this separation is materialized through an infrastructure of distantiation built around COI production sites. This apparatus is discernible not only in discourses and practices, but also in the organizational structures, spaces, and legal norms that contribute to the ecology of this specific site of expert knowledge production. It participates in the construction of the legitimacy of both institutions and individual actors involved in knowledge production.
Keywords: Country of origin information; COI; Asylum procedures; Refugee status determination; Legitimisation; Distantiation; Expertise; Ecology of knowledge